Mediating role of service quality between university social responsibility and student satisfaction in Peru - Isac Fernando Espinoza Montes; Nérida Pilar Zevallos Cárhuaz; Martin Romeo Yurivilca Oscanoa (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study analyzed the influence of university social responsibility (USR) on student satisfaction (SS), mediated by service quality (SQ). It is relevant because it provides empirical evidence of how socially responsible practices strengthen educational quality and student well-being in a Latin American context that remains underexplored through structural equation modeling (SEM). The objective was to explain how USR affects SS through SQ, using SEM. Specifically, the study examined the direct effect of USR on SS, its influence on SQ, the impact of SQ on satisfaction, and the mediating role it plays in this relationship. A quantitative, non-experimental, cross-sectional design was employed with a sample of 505 undergraduate students from five Peruvian public and private universities, selected through non-probability convenience sampling. Data were collected using three validated and reliable Likert-type scales. The results showed that USR significantly influenced SQ (R²=0.60) and that SQ predicted SS (R²=0.67), confirming a partial mediation effect. The findings provide practical implications for strengthening institutional policies to enhance SQ and increase SS.